The impact of lockdowns during the COVID-19 pandemic on fertility intentions - Mooi-Reci, Irma; Trinh, Trong-Anh; Vera-Toscano, Esperanza; Wooden, Mark (My University, 2023)
Lockdown edicts during the COVID-19 pandemic have led to concerns about consequences for childbirth plans and decisions. Robust empirical research to either refute or confirm these concerns, however, is lacking. To evaluate the causal impact of lockdowns on fertility, we exploited a large sample of Australians (aged 18 to 45) from a nationally representative household panel survey and leveraged variation from a unique natural experiment that occurred in Australia in 2020: a lockdown imposed in the state of Victoria, but not elsewhere in Australia. Difference-in-differences models were estimated comparing changes in fertility intentions of persons who resided in Victoria during lockdown, or within four weeks of the lockdown being lifted, and those living elsewhere in Australia. Results revealed a significantly larger decline in reported intentions of having another child among women who lived through the protracted lockdown. The average effect was small, with fertility intentions estimated to fall by between 2.8% and 4.3% of the pre-pandemic mean. This negative effect was, however, more pronounced among those aged over 35 years, the less educated, and those employed on fixed-term contracts. Impacts on men’s fertility intentions were generally negligible, but with a notable exception being Indigenous Australians.
Economics & Human Biology
Keywords: Families and relationships; Government, law and policy